Comparative Analysis of Euclid and Lobachevsky Geometries (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the article, Lobachevsky geometry is a widely applied theory in mathematics, mechanics and physics. This geometry is important because it is a geometric theory based on a cistern of axioms, which differs from the system of axioms of Euclidean geometry only by the axiom of parallelism. The role of Euclid in the field of mathematics, the principal separation of geometry from arithmetic, planametry from stereometry, has been studied.